Durability of tissue-engineered bovine pericardium (CardioCel®) for a minimum of 24 months when used for the repair of congenital heart defects. (7th August 2018) - Bell, Douglas; Prabhu, Sudesh; Betts, Kim; Justo, Robert; Venugopal, Prem; Karl, Tom R; Alphonso, Nelson
Abstract: OBJECTIVES: This study aims to assess the performance of tissue-engineered bovine pericardium (CardioCel ® ) at 24 months and beyond when used for the repair of congenital heart defects. METHODS: Between October 2012 and November 2014, CardioCel was implanted in 135 patients (140 procedures and 195 implants). Applications included the closure of septal defects (98, 50.3%), repair of pulmonary arteries (63, 32.3%), intra-atrial/intraventricular baffles (10, 5.1%), repair of systemic arteries (15, 7.7%), valve repair (5, 2.6%), repair of systemic veins (3, 1.5%) and Fontan operation (1, 0.5%). There were 19 (13.6%) procedures performed in neonates, 77 (55%) in infants and 44 (31.4%) in children older than 365 days. RESULTS: Eight patients ( n  = 135, 5.9%) required reintervention in 12 instances ( n  = 195, 6.2%, 6 catheters and 6 surgical). There was no echocardiographic or radiological evidence of calcification in any patient. Ten of the reinterventions (83%) occurred within the first 12 months. All the reinterventions occurred within 36 months. Freedom from reintervention at both 12 and 24 months was 95% [confidence interval (CI) 91–97] and at 36 months was 94% (CI 89–97). There was no statistical difference in freedom from reintervention when stratified by age or patch position. CONCLUSIONS: At 24 months and beyond the follow-up, the performance of CardioCel remains acceptable with good haemodynamic performance. There was no echocardiographic or radiological evidence of calcification in any patient. CardioCel performs comparably in systemic and pulmonary circulations.